Growth and sintering effects of hydrated polycrystalline Li2WO4 - Johan, M.R.; Han, T.K.; Arof, Abdul Kariem (Springer Verlag (Germany), 2010)
Polycrystalline Li2WO4 was sintered at temperatures, 400, 450, 500, 550, 600, 650, and 700 A degrees C. After sintering at each particular temperature, the Li2WO4 was cooled to room temperature. The X-ray diffraction pattern of Li2WO4 exhibits dominant peaks attributable to 7Li(2)WO(4).4H(2)O (cubic) and Li2WO4 (hexagonal) and thus reveals the extent of hydration of the material. The composition varies on heating at several temperatures as shown by the presence of new peaks in the diffractogram. Thermogravimetric analysis is used to correlate respective structural and thermal properties in variation. The impedance spectra show the presence of a semicircle in the higher frequency regions and straight line behaviors at lower frequencies. SEM micrographs depict the image of sintered Li2WO4. Grain growth studies reveal the sensitiveness of grain toward temperature. The maximum grain size is observed to be a parts per thousand 5.7 mu m at 700 A degrees C.